Differential tolerance of crotalaria species to herbicides - Malardo, Marcelo Rafael; Monquero, Patricia Andrea; da Silva, Paulo Vinicius; Silva Hirata, Andreia Cristina (Comunicata Scientiae, 2018)
Annual crops and crotalaria intercropping has been used to control nematodes. The evaluation of the susceptibility of crotalaria species to herbicides is an important step to make this technology viable. The aim of this experiment was to determine the tolerance of Crotalaria juncea, C. ochroleuca, C. spectabilis and C. breviflora to pre and post-emergence herbicides. Post-emergence (bentazon, ametryn, amicarbazone, 2,4-D amine and mesotrione) and pre-emergence herbicides (atrazine + mesotrione, atrazine + simazine, atrazine, isoxaflutole, pendimenthalin, s-metolachlor and trifluralin) were evaluated in doses of 0.5D; 0.75D; 1D and 1,25D; in which D was the commercial dose of each product. The results demonstrated that the species of crotalaria differ on the susceptibility to pre and post emergence herbicides. Among the post-emergence herbicides, bentazon showed higher selectivity. However, reduced doses of some post-emergence herbicides can make the intercropping with some species of crotalaria viable. The most selective pre-emergence herbicides were pendimenthalin, s-metolachlor and trifluralin. In general, C. spectabilis was the most susceptible to the evaluated herbicides.